The Impact of Solo Safari’s Rebranding on Public Perception and the Sustainability of Conservation-Based Tourism - Sri Wijiastuti; Kurniawati Darmaningrum; Novita Aryani; Sativa Isaach (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to examine the impact of Solo Safari’s rebranding on public perception, marketing effectiveness, and local community involvement in sustainable conservation tourism. Methodology: A qualitative case study method was used. Data collection tools included semi-structured interviews, observation, and document review. Analysis was conducted using thematic analysis with support from NVivo 12 software. Data were sourced from visitors, community members, and management. Main Findings: The study found that 83% of visitors positively perceived the rebranding. Instagram followers increased by 72%, and community involvement rose to 60%. Public perception, marketing performance, and local economic benefits significantly improved post-rebranding. The rebranding enhanced brand equity, visitor satisfaction, and community pride. Novelty/Originality of this study: This study integrates brand equity theory with community-based tourism in a local conservation context to examine how destination rebranding affects both marketing performance and social sustainability. Using a mixed-methods approach that combines visitor surveys and stakeholder interviews, the research finds that Solo Safari’s rebranding has significantly improved its brand image, visitor engagement, and perceived conservation value. A key novelty of this study lies in its dual focus—demonstrating, for the first time in the local context, how rebranding can serve as a strategic bridge between market-oriented goals and inclusive community participation, thereby advancing both destination competitiveness and conservation-driven social sustainability.